Eccrine porocarcinoma with squamous differentiation in a patient with oculocutaneous albinism - Biswajit Dey; Vandana Raphael; Caleb Harris (Wolters Kluwer Medknow Publications, 2020)
Eccrine porocarcinoma is a rare malignant skin appendage tumor of sweat gland origin. Eccrine porocarcinoma arising in a patient of oculocutaneous albinism is extremely rare and only two cases have been reported in English literature to the best of our knowledge. Out of the two cases of eccrine porocarcinoma in oculocutaneous albinism, one case had squamous differentiation. We report a case of eccrine porocarcinoma with squamous differentiation in a 39-year-old male, who presented with a nodular lesion on the upper left chest wall. He also had nodal and distant cutaneous metastasis.